(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 52-year-old female was admitted to the hospital with chronic diarrhoea, vomiting, and weight loss. She also reported dyspnea on exertion, palpitation, and hypertension. She had recently been diagnosed with Grave’s thyrotoxicosis with carbimazole-induced agranulocytosis with lithium toxicity. Physical examination revealed signs of thyrotoxicosis with right heart failure with atrial fibrillation. Thyroid gland examination revealed a diffuse, firm, nontender goiter. On cardiovascular examination, a grade III pansystolic murmur in the mitral area was found. ECG showed atrial fibrillation. Transthoracic echocardiography showed a flail posterior mitral leaflet (PML) with severe mitral regurgitation (MR). After initial conservative treatment, radioactive iodine ablation was done and her dyspnea, leg edema and diarrhoea gradually improved and she achieved stable thyroid and cardiac function with β blocker only. A follow-up visit after 6 months documented the absence of cardiac symptoms. There were no murmurs clinically and only mild MR on echocardiography. This case demonstrates the importance of cardiac evaluation in hyperthyroidism as treatment of thyroid abnormalities can reverse these cardiac manifestations. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023; 2 (1): 24-27